Typology of Metaphor Transfer Techniques (German Translation of A.I. Solzhenitsyn’s ‘The Gulag Archipelago’) - M. L. Alekseyeva; V. E. Salo (Научный диалог)
In this article, we propose an original typology of metaphor transfer techniques based on the analysis of domestic and foreign translation theorists’ experience. The relevance of the study lies in the need to review existing classifications of techniques, unify terminology, identify principles of systematization, and clarify the scope and content of translation operations. The novelty of the research lies in the description of a new developed typology, which structures techniques according to types based on the principle of preserving the original figurative basis, and subtypes depending on the method of transferring form and content, as well as reproducing extralinguistic components. The methodological basis of the study is classification, as well as a comparative analysis of original metaphors and their translations, conducted with the support of a definitional analysis of metaphorically used lexical units, contextual and component types of analysis. The application of the typology on the German translation of A. I. Solzhenitsyn’s ‘The Gulag Archipelago’ (A. Peturnig, 1974), accompanied by translation commentaries, has shown that all examined techniques have the potential to ensure a high degree of adequacy in translation, with the core being the reproduction of pragmatic effect and successful implementation of communicative tasks.